Genetic Algorithm Based Lightning Estimation Model - Musse Mohamud, Ahmed; Mohammad Kamrul, Bin Hasan; Jong, F. Chen; Denis, Lee (Institute of Mechanics of Continua and Mathematical Sciences, 2020)
When lightning strikes to the transmission line, orifices in the insulation can be created. As a result, the insulation co-ordination between phases is breakdown and over-voltage will propagate across the transmission line in the form of electrical fields. Hence, the system will encounter under-frequency and prolonged type of destruction. In a worst-case situation, it may lead blackout. One of the effective ways to reduce lightning impact is to identify the lightning activity. This researchhas been carried out to familiarize the lightning activity in Sarawakarea;hence, the Genetic Algorithm (GA) is utilized to optimize the crucial constants of the lightning empirical equation. As the constant values are successful to be optimized, estimation of Ground Flash Density (GFD) can be performed. The performance is evaluated using Matlab. Using the GA optimized parameter the estimations areprecise. To achieve estimation that is more accurate many trials are required to be carried out in order to determine the best fitness value. In this article, three casesare carried out in determining the optimal solution in term of constant “a” and “b” for each sub-region in Sarawak.